Safety Considerations Regarding to the Shielding of Electric Fields During High Voltage Live-line Maintenance - Göcsei, G.; Berta, I.; Németh, B. (Acta Technica Jaurinensis, 2015)
Live-line maintenance (LLM) has several technical and economic benefits. Planned works can be executed without any consumer disturbance, while the network is energized. Strict regulations regarding to the working method, well-educated workers and well-considered safety factors ensures the high level of safety of this technology. Although statistics show that the number of injuries is lower than in case of de-energized works, the unseen short- and long term effects of electric and magnetic fields also have to be taken into consideration.